KARAKTERISTIK IBU HAMIL DENGAN PREEKLAMPSIA DI RSUD dr. R. GOETENG TAROENADIBRATA PURBALINGGA TAHUN 2007 - Erni Setiawati; Fitria Zuhriyatun (Universitas Harapan Bangsa Purwokerto, 2008)
Background: Maternal mortality rates in the world is still very high, maternal mortality is caused by infection, eclampsia and hemorrhage, in hospitals. dr. R. Goeteng TaroenadibrataPurbalingga the incidence of preeclampsia in the year 2007 as many as 71 cases.Objective: To determine the characteristics of pregnant women with preeclampsia inhospitals.dr. R. Goeteng Taroenadibrata Purbalingga 2007.Method: quantitative descriptive study using a retrospective approach, the population in thisstudy were all pregnant women who experience preeclampsia who are 71 pregnant women, witha total sampling sampling technique, the instrument used is the master table.Results: The characteristics of pregnant women with preeclampsia are 71 pregnant, where themajority of pregnant women aged mostly mothers in the age group of 20-35 years that therewere 36 pregnant women (51%) and the lowest is at age <20 years which is contained 18pregnant women (11%) based on gestational age is largely the third trimester (29-40 Sunday) of50 pregnant women (70%) based on the parity most cases dominated in multiparasPreeclampsia is 33 mothers (46%) and the lowest is Grande multiparas 14 pregnant women(20%), based on the history of the disease largely dominated by the mother who does not hurtthat 54 pregnant women (76%) and the sick 17 pregnant women (24%).Conclusion: The characteristics of pregnant women with preeclampsia in the mother can be apercentage based on the age group of 20-35 years by 51%, based on the gestational age at thethird trimester group by 70%, Based on Parity in multiparas by 46%, based on the history of thedisease in pregnant women is not pain by 76% and the pain of 24%.Keywords: Characteristics, pregnant women, preeclampsia.